Phyto-pharmacological evaluation and characterization of the methanolic extract of the Baccaurea motleyana Müll. Arg. seed: promising insights into its therapeutic uses - Shompa, Suriya Akter; Hasnat, Hasin; Riti, Saima Jahan; Islam, Md. Mirazul; Nur, Farjahan; Alam, Safaet; Shao, Chuxiao; Wang, Shuanghu; Geng, Peiwu; Mamun, Abdullah Al (Frontiers in Pharmacology, 2024)
Introduction: Plants and their extracts have been integral to the development of medicinal treatments throughout history, offering a vast array of compounds for innovative therapies. Baccaurea motleyana Müll. Arg., commonly known as Rambai, is an evergreen tree with economic importance in the Old-World Tropics. Method: The study investigates its phytochemical composition through Gas Chromatography-Mass Spectrometry (GC-MS) and evaluates its pharmacological properties, including antidiabetic, antidiarrheal, antimicrobial, and antidepressant effects. Result and Discussion: The GC-MS analysis revealed 15 bioactive compounds in the methanol extract, with Phenol, 3,5-bis(1,1-dimethylethyl)-, Methyl stearate, and Hexadecanoic acid, methyl ester being the predominant ones. The cytotoxicity assay demonstrated significant activity in the ethyl acetate fraction. Antimicrobial assays indicated mild to moderate antibacterial activity. In vivo studies on mice revealed significant hypoglycemic, antidiarrheal, and antidepressant properties. Molecular docking studies against EGFR, DHFR, GLUT-3, KOR, and MOA identified promising compounds with potential therapeutic effects. The identified compounds exhibited favorable ADME/T properties, emphasizing their potential for drug development. The study underscores the promising therapeutic potential of Baccaurea motleyana, showcasing its diverse bioactive compounds with significant medicinal properties. Conclusion: These findings lay the groundwork for future research, emphasizing the exploration of B. motleyana as a source of natural remedies for addressing prevalent health conditions.